2000
DOI: 10.2460/ajvr.2000.61.684
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiologic correlates of acute porcine pleuropneumonia

Abstract: Endotracheal inoculation with A pleuropneumoniae rapidly and consistently induced diffuse bilateral pneumonia; thus, this method may be useful for the study of acute pathophysiologic changes associated with bacterial pneumonia and may provide an experimental model for testing modalities for prevention and treatment of this and other respiratory tract diseases of pigs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 26 publications
1
46
0
Order By: Relevance
“…Cytokine expression, such as Interleukin-6, is brief and of less magnitude than APPs (Hulten et al, 2003). Compared with leucocytes, APPs may offer an improved diagnostic sensitivity as pigs with clinical signs and severe pathological lesions did not develop leucocytosis but had elevated APPs concentrations (Baarsch et al, 2000;Lauritzen et al, 2003b). In addition, they are more stable than blood cells and assays can be performed on frozen serum or plasma samples.…”
Section: Discussionmentioning
confidence: 97%
“…Cytokine expression, such as Interleukin-6, is brief and of less magnitude than APPs (Hulten et al, 2003). Compared with leucocytes, APPs may offer an improved diagnostic sensitivity as pigs with clinical signs and severe pathological lesions did not develop leucocytosis but had elevated APPs concentrations (Baarsch et al, 2000;Lauritzen et al, 2003b). In addition, they are more stable than blood cells and assays can be performed on frozen serum or plasma samples.…”
Section: Discussionmentioning
confidence: 97%
“…The samples were purified on a Bio-Gel P-2 column as described previously (12). Core fractions (fractions 19 -24) eluting off the column slightly after the O-chain (fractions [15][16][17] were combined and lyophilized.…”
Section: Methodsmentioning
confidence: 99%
“…The innate immunity is the first barrier for invading organisms, and inflammation is known to be of special importance in this first line of defense (16). Porcine pleuropneumonia is characterized by an intensive inflammation with infiltration of phagocytic cells such as neutrophils and alveolar macrophages, which are the main cells found in affected lungs (17). Previous in vivo studies have shown that A. pleuropneumoniae infection is associated with the production of a large amount of inflammatory mediators (18,19) and proinflammatory cytokines such as IL1, TNF-␣, IL8, and IL6 (20,21) that could be responsible, at least in part, for the lung injuries and tissue destruction observed in porcine pleuropneumonia (20,22).…”
mentioning
confidence: 99%
“…Four-to six-week-old (8 to 10 kg) male pigs were obtained from a pleuropneumonia-negative commercial herd. Animals were anesthetized with telazole (10 mg/kg of body weight) (Fort Dodge Laboratories, Fort Dodge, Iowa) and treatments were administered intratracheally via the CO 2 port of an ETCO 2 tracheal tube (Sheridan Catheter Corp., Argyle, N.Y.) as previously described (3).…”
Section: Methodsmentioning
confidence: 99%